HEARING HANDICAP IN OLDER ADULTS: A MULTI-CENTER STUDY - Zahra, Gul -e-; Saqulain, Ghulam; Mumtaz, Nazia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the level of hearing handicap and its age and gender association in older adults.Study Design: Cross sectional analytical study.Place and Duration of Study: Study conducted at Ear, Nose & Throat outpatients of Yusra General Hospital, National Institute of Rehabilitation Medicine Islamabad and Cantonment General Hospital Rawalpindi, from Jul to Sep 2017.Methodology: We recruited two hundred cases of self-reported hearing difficulty, using non-probability consecutive sampling, who fulfilled inclusion criteria. After recording demographic details including history, subjects were screened by the Screening Version of Hearing Handicap Inventory for the Elderly (HHIE-S). Followed by otoscopy and pure tone audiometry. Analysis was done using SPSS-24.Results: Study revealed 133 (65.5%) males and 67 (33.5%) females with mean age of 65.45 ± 7.50 years. Out of 179 (89.5%) had significantly high level of hearing handicap with HHIE-S score >43, while 21 (10.5%) revealed mild to moderate handicap with score of 17-42. Hearing handicap was significantly associated with aging (p